Analisis Metode Reading Aloud Dalam Pembelajaran Literasi Siswa Sekolah Dasar - Farida Agil Arianti; Badruli Martati; Deni Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
This research was conducted with the aim of knowing how to describe the application of the reading aloud method in class II Al - Barii' in literacy learning at SD Muhammadiyah 8 Surabaya. The approach taken in this study is to use a qualitative approach with a descriptive approach. Data collection techniques based on the results of interviews, observations, and documentation. The data analysis technique for this study uses miles and huber data analysis, namely by data reduction, data presentation, and drawing conclusions. The results of this study will show how to apply the reading aloud method and also find out the results of student literacy learning. it can be concluded that from the application of the reading aloud method it can have an influence on literacy learning for class II Al - Barii' SD Muhammadiyah 8 Surabaya students. Learning children's literacy with read aloud activities has a good or positive impact. There were no students who did not like this activity. All students like to read stories aloud.